TEKNOLOGI TEPAT GUNA BERBASIS ENERGI SURYA SEBAGAI INOVASI PENINGKATAN POTENSI DESA WISATA: APPROPRIATE TECHNOLOGY BASED ON SOLAR ENERGY AS AN INNOVATION TO ENHANCE THE POTENTIAL OF TOURISM VILLAGES - Ilahi, Novita Asma; Purnata, Hendi; Rahmat, Saepul; Widianingsih, Betti; Karyani, Uli (Universitas PGRI Yogyakarta, 2023)
Widarapayung Wetan is one of the innovation villages in Cilacap Regency with the method of developing a one-stop destination tourist area. The development of tourist areas certainly attracts visitors and the public to be able to gather and have activities at the same location. This innovation certainly requires various facilities and infrastructure to support development. To support the government's program in developing the use of new and renewable energy and developing an innovation village in the village of Widarapayung Wetan, an infrastructure to support visitor facilities was made in the one-stop destination tourist area of ​​Widarapayung Wetan Village. The Solar Electric Device Charging Station (S – EDCS) uses solar system technology so that it will not burden the use of PLN's electrical energy. The use of solar energy also provides knowledge for the surrounding community to be able to innovate to develop electricity needs using the S – EDCS tool which is implemented in the village of Widarapayung Wetan. The installation of S – EDCS is a Social Innovation for the community that has not existed before in Widarapayung Wetan Village.